Disaster Risk Management in Mountain Tourist Destinations in Chile: The Case of El Yeso Reservoir - Claudia González-Muzzio; Claudio Rozas Vidal (Revista de Estudios Latinoamericanos sobre Reducción del Riesgo de Desastres, 2020)
In recent years, there has been a progressive increase in the importance of tourism as an engine of local economic development in Chile and, in particular, of mountain destinations. This is being driven by various policies and programs at national, regional and local levels. However, these territories are highly exposed to geological and hydrometeorological hazards, in addition to be considered environmentally sensitive areas. Thus, sustainable development of tourism urgently requires a comprehensive management of risks associated to mountain activities, and considering institutional actors, tour operators, and, particularly, visitors. From a regional planning view, it seems irresponsible to promote tourism activity without considering, on the one hand, the effect of it on the environment and, on the other, the hazards that may affect the economic and social development that is being promoted as well as the workers themselves and especially tourists. By examining El Yeso reservoir case study in the mountain range of the Metropolitan Region, this paper explains the limitations and challenges for a sustainable tourism in mountain destinations in the country.